The effect of green innovation , green house gas emission , and environmental performance on firm value - NURUL FITRAH ISLAMIAH; DARWIS SAID; SRI SUNDARI (International Journal of Multidisciplinary Research and Studies, 2023)
This study looks at whether green innovation, greenhouse gas emissions, and environmental performance can affect company value. Companies included in the observation are SRI-KEHATI index companies from 2018 to 2022. The SPSS 26 application is used in this research's quantitative methodology to process panel data. A purposive sampling technique was used to select a sample with a total of 16 selected companies. The study observed company reports for 5 years, namely 2018-2022, so there were a total of 80 observations made for this study. The Indonesian Biodiversity Foundation website (www.kehati.or.id), the official websites of each company, and the IDX website (www.idx.co.id) were used to obtain secondary data for this study. Normality tests, multicollinearity tests, and heteroscedasticity tests have been used to validate the data. According to this study, greenhouse gas emissions and green innovation both have a significant impact on company value. The value of the company will increase along with the increase in green innovation, conversely, the value of the company will decrease if greenhouse gas emissions increase. While environmental performance has no significant effect on firm value.